A BIOCHEMICAL TEST FOR THE DISTINCTION OF FRESH FISH FROM FROZEN AND THAWED FISH - CHHATBAR, SUDHIR K; VELANKAR, N K (Fishery Technology, 2017)
It is observed that the freezing and thawing of fish leadsto increase in the total activity of aspartate aminotransferase(AAT) in tissue finid due to the release of the bound formnf mitochondrial enzyme. Electrophoresis of the tissue fluid offresh ur:frozen fish shows only a single fast-moving band ofAAT in the anod:c region whereas frozen and thawed fishshows an additional slow-moving band corresponding to mitochondrialAAT in the cathodic region. The method can beadopted to distinguish fresh fish from frozen and thawed fish.